Teaching and Researching Genre Knowledge: Toward an Enhanced Theoretical Framework. (July 2020) - Tardy, Christine M.; Sommer-Farias, Bruna; Gevers, Jeroen
Increased attention to genre in writing studies has brought a proliferation of new terms and concepts for capturing the complexity of writers' knowledge about genres, including genre knowledge, genre awareness, recontextualization, conditional knowledge, and metacognition. Definitions of these concepts have at times conflicted, and their interrelationships are often unclear. Furthermore, scholarship has tended to overlook the role of multiple languages in writers' genre knowledge. In this article, we first trace the use of related terminology and demonstrate the need for theoretical clarity. We then propose a theoretical framework that articulates key layers of genre knowledge and their interrelations, presuming a multilingual writer. Finally, we share examples of how this proposed framework may be used in teaching and researching genre knowledge. Ultimately, we aim to contribute to ongoing theoretical, empirical, and pedagogical explorations and applications of knowing and learning genres.